Admission of Morocco into ECOWAS: Implications for Nigeria’s National Interests, ECOWAS, and EU. - Bakare, Olukayode (IJRDO - Journal of Social Science and Humanities Research, 2019)
This paper seeks to examine the theoretical constructs under which the Moroccan membership within the ECOWAS demonstrates and poses tension, rivalries, leadership supremacy and challenges in the West African region. The puzzle in the context of this paper is to offer theoretical views and examination of key concepts, such as national interests, and foreign policy that are critical to the perspectives of the dynamics of state actors in the international system and how these are relevant to the Moroccan foreign policy in ECOWAS, Nigerian national interests and the European Union (EU).